Spark Plasma Sintering of Si3N4/C Composites - Taslicukur, Zeynep; Sahin, Filiz Cinar; Goller, Gultekin; Yucel, Onuralp; Kuskonmaz, Nilgun (CARL HANSER VERLAG, 2010)
Si3N4/C composites were prepared with carbon black and alpha-Si3N4 powder by a novel sintering method, i. e. spark plasma sintering. SiC particles formed through reactions between the carbon particles and the SiO2 on the Si3N4 surface. The samples were sintered at 1650 degrees C for 5 minutes in a nitrogen atmosphere. The microstructure, phase composition, mechanical properties, and dielectric properties of the composites were investigated. The relative densities of the C/Si3N4 composites decreased from 99 to 85 % when the carbon black content increased from 0 to 20 wt.-%. Bending strength, hardness and dielectric properties were found to be influenced by the amount of carbon black introduced into the silicon nitride matrix.
Keywords: CERAMICS; SILICON; Materials Science